The Effects of Biological Augmentation with Platelet-Rich Plasma on Graft Healing and Clinical Outcomes in Arthroscopic Assisted Anterior Cruciate Ligament Reconstruction - Qureshi, Bilal Ahmad; Amin, Muhammad Suhail; Rathore, Muhammad Omar; Hussain, Asad Moiz (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the clinical and radiological effects of platelet-rich plasma on graft maturation applied during anterior cruciate ligament reconstruction with bone–patellar-tendon–bone autograft. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Orthopedic Surgery, Combined Military Hospital Rawalpindi, Pakistan from Oct 2022 to Sep 2023. Methodology: A total of 40 patients, aged 18 to 50 years, with unstable symptomatic knee and complete anterior cruciate ligament tear, were sequentially enrolled into two groups. Arthroscopic anterior cruciate ligament reconstruction with patellar tendon autograft was conducted on all knees using the same protocol with the addition of platelet-rich plasma to the graft in Group A (PRP Group), and no PRP was added in Group B (control group). Follow-up visits occurred postoperatively every 4 weeks. The IKDC Scoring Scale and Lysholm Knee Scoring Scale were included to compare functional status, and an MRI was conducted 3 and 6 months after surgery to assess graft maturation. Results: Anterior cruciate ligament reconstruction with the use of platelet-rich plasma achieves more diffusely hyperintense grafts assessed by MRI at 3 and 6 months, compared to anterior cruciate ligament reconstruction without platelet-rich plasma. At 3 and 6 months, 5(25%) and 9(45%) grafts were diffusely hyperintense in PRP group (p=0.03. p=0.04). Moreover, the platelet-rich plasma group showed a statistically significant improvement in clinical score at 3-month intervals only with mean IKDC Score being 66.9±4.8 (p=0.001) and mean Lysholm Score being 70.0±6.8 (p=0.01). Conclusion: Patellar tendon graft remodeling seems to be accelerated by platelet-rich plasma, but has only short-term